BRIDGING TECHNOLOGY AND LITERATURE: A FLIPBOOK-BASED INTERVENTION FOR CHILDHOOD LITERACY DEVELOPMENT - Fitri Puji Rahmawati; Vera Herapuspita (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study aims to develop and test the feasibility of digital-based Children’s Story Flipbook media as a means of strengthening literary literacy in Indonesian language learning in elementary schools. This study uses a qualitative approach with the Research and Development (R&D) method that refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted at Muhammadiyah Plus Malangjiwan Elementary School with research subjects including fifth-grade students, class teachers, the principal, and expert validators of media, language, and materials. Data collection techniques were carried out through observation, interviews, questionnaires, literary literacy comprehension tests (pre-test and post-test), and documentation. The results showed that the digital-based Children’s Story Flipbook media was declared suitable for use based on the validation results of media experts by 96%, language experts by 95.78%, and material experts by 100% with a very good category. The implementation of media in learning showed an increase in students’ literary literacy understanding, marked by an increase in the average pre-test score of 56% to 95% in the post-test. Furthermore, the use of flipbooks can increase students’ interest in reading, active engagement, and understanding of the elements and moral values in children’s stories. Therefore, digital-based flipbooks for children’s stories are effective as a learning medium for literary literacy in elementary schools.